First looks at solar active regions with ALMA - Loukitcheva, Maria; Reardon, Kevin P. (Frontiers in Astronomy and Space Sciences, 2022)
During the first few years of observing the Sun with the Atacama Large Millimeter/submillimeter 4 Array (ALMA), the scientific community has acquired a number of observational datasets targeting 5 various structures in active regions, including sunspot umbra and penumbra, active region pores, 6 and plages. In this paper we review the results obtained from the extensive analysis of these 7 interferometric millimeter data, together with the coordinated observations from IRIS, SDO, IBIS, 8 and Hinode, that reveal information on the chromospheric thermal structure above active regions 9 and properties of small-scale heating events near magnetic field concentrations. We discuss the 10 properties of waves (especially the three-minute oscillations) in sunspots, plage, and network. We 11 speculate how high-resolution millimeter data can supplement spectral line observations in the 12 visible and UV and can improve chromospheric spectroscopic inversions. We identify challenges 13 in the interpretation of the millimeter continuum emission due to the complex, non-local and 14 time-dependent processes that determine the electron density through the chromosphere. Finally 15 we overview the prospects for future active regions observations with ALMA during the ascending 16 phase of the solar cycle.